1993
DOI: 10.1093/jn/123.11.1859
|View full text |Cite
|
Sign up to set email alerts
|

Corandomization of Fats Improves Absorption in Rats

Abstract: Human milk fat is well absorbed despite its large concentration of long-chain saturated fatty acids (LCSFA), particularly palmitic acid. The superior absorption has been ascribed in part to the uncommonly high proportion of the palmitic acid in the sn-2 position of the triglycerides, 70% in human milk triglycerides compared with 10-15% in the fats and oils commonly used in infant formula blends. Colipase-dependent pancreatic lipase selectively hydrolyzes the fatty acids at the sn-1 and 3 positions, yielding fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
30
0
2

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 20 publications
5
30
0
2
Order By: Relevance
“…Similar results had been obtained in preterm infants (Carnielli et al, 1995) and rats (Aoyama et al, 1996;de Fown et al, 1994;Lien et al, 1993;Renaud et al, 1995;Tomarelli et al, 1968).…”
Section: Fatty Acid Composition Of Infant Formulassupporting
confidence: 84%
See 1 more Smart Citation
“…Similar results had been obtained in preterm infants (Carnielli et al, 1995) and rats (Aoyama et al, 1996;de Fown et al, 1994;Lien et al, 1993;Renaud et al, 1995;Tomarelli et al, 1968).…”
Section: Fatty Acid Composition Of Infant Formulassupporting
confidence: 84%
“…Palmitic acid was also absorbed more with formulas rich in palmitic acid esterified at the sn-2 position of the triglycerides than with formulas containing palmitic acid largely esterified to the sn-1, 3 positions. These results were obtained in studies carried out on term infants (Carnielli et al, 1996;Filler et al, 1969), preterm infants (Carnielli et al, 1995) and rats (Aoyama et al, 1996;de Fown et al, 1994;Lien et al, 1993;Renaud et al, 1995;Tomarelli et al, 1968). Moreover, the location of palmitic acid in the sn-2 position in infant formulas improves the absorption of calcium in the small intestine (Lucas et al, 1997;Carnielli et al, 1996;Nelson et al, 1996).…”
Section: Introductionmentioning
confidence: 86%
“…N eanmoins, une meilleure absorption (2 a 3 fois moins d'excr etion f ecale) du C16:0 (mais aussi du C14:0 et C18:0) a et e observ ee apr es augmentation de sa proportion en position sn-2 par interest erification de TAG d'huile de noix de coco et de palme (Lien et al, 1993). Des r esultats similaires ont et e obtenus chez le porcelet lorsque le C16:0 est majoritairement est erifi e en position sn-2 des TAG en comparant de l'huile de palme et du saindoux, natifs ou interest erifi es (Renaud et al, 1995) ou des formulations laiti eres (Innis et al, 1995(Innis et al, , 1997.…”
Section: Desunclassified
“…Previous studies have shown that fats with saturated fatty acids on the sn-2 position are better absorbed [1,2] and they result in slower chylomicron clearance rates [3,4] than those with saturated fatty acids on the sn-1,3 positions. This likely contributes to a more pronounced and prolonged postprandial and fasting lipemia.…”
Section: Introductionmentioning
confidence: 99%